Towards optimized tissue regeneration: a new 3D printable bioink of alginate/cellulose hydrogel loaded with thrombocyte concentrate - Grandjean, Till; Perumal, Natarajan; Manicam, Caroline; Matthey, Björn; Wu, Tao; Thiem, Daniel G. E.; Stein, Stefan; Henrich, Dirk; Kämmerer, Peer W.; Al-Nawas, Bilal; Ritz, Ulrike; Blatt, Sebastian (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Autologous platelet concentrates (APC) are pro-angiogenic and can promote wound healing and tissue repair, also in combination with other biomaterials. However, challenging defect situations remain demanding. 3D bioprinting of an APC based bioink encapsulated in a hydrogel could overcome this limitation with enhanced physio-mechanical interface, growth factor retention/secretion and defect-personalized shape to ultimately enhance regeneration. Methods: This study used extrusion-based bioprinting to create a novel bioink of alginate/cellulose hydrogel loaded with thrombocyte concentrate. Chemico-physical testing exhibited an amorphous structure characterized by high shape fidelity. Cytotoxicity assay and incubation of human osteogenic sarcoma cells (SaOs2) exposed excellent biocompatibility. ELISA analysis confirmed pro-angiogenic growth factor release of the printed constructs, and co-incubation with HUVECS displayed proper cell viability and proliferation. Chorioallantoic membrane (CAM) assay explored the pro-angiogenic potential of the prints in vivo. Detailed proteome and secretome analysis revealed a substantial amount and homologous presence of pro-angiogenic proteins in the 3D construct. Results: This study demonstrated a 3D bioprinting approach to fabricate a novel bioink of alginate/cellulose hydrogel loaded with thrombocyte concentrate with high shape fidelity, biocompatibility, and substantial pro-angiogenic properties. Conclusion: This approach may be suitable for challenging physiological and anatomical defect situations when translated into clinical use.